Determination of some heavy metals in cosmetic products collected from Benghazi-Libya markets during 2016 - Rahil, Salwa; Elshara, Intisar; Ahmida, Nagwa; Ahmida, Mohamed (Libyan International Medical University Journal, 2019)
Introduction: Cosmetics have been utilized by most of the people irrespective of their race, gender, or age to beautify, modify, or improve the physical appearance. Many cosmetic products contain heavy metals as ingredients or impurities. Recent research has reported that these metals can cause many types of health and skin problems. Aims: The aim of this study is to detect the levels of heavy metals in some cosmetic products that are available in cosmetic shops around the city of Benghazi. Materials and Methods: Twenty-five of cheap facial cosmetic products that are widely in demand in cosmetic shops in Benghazi were collected in April 2016. The samples included eight kohl, seven eyeliners, and ten lipsticks. Metals including iron, copper, chromium, zinc, lead, and cadmium were analyzed in the selected samples using flame atomic absorption spectrophotometer after suitable digestion process. Results: Our results indicated that iron and copper were detected in all samples with concentration ranges varying from 0.5 to 124.5 mg/kg for iron and 1.8–51.4 mg/kg for copper. The concentration ranges of chromium, zinc, cadmium, and lead were varied from 0.0 to 7.25 mg/kg, 0.0 to 22.75, 0.0 to 125.0 mg/kg, and 0.0 to 20.25 mg/kg, respectively. Conclusions: The results showed that the selected metals were detected in most of the samples at varying concentrations. Kohl samples have the highest concentration of the analyzed metals. According to the maximum allowed limits recommended by the World Health Organization (WHO) for toxic metals in cosmetics, there was only one sample that had lead concentration higher than the maximum limit recommended by the WHO. In addition, there were twenty samples that had concentrations of cadmium above the WHO legislation limits.
Keywords: Benghazi; cosmetic products; eyeliner; heavy metals; kohl; lipstick